Molecular evidence that Heligmosomoides polygyrus from laboratory mice and wood mice are separate species - Cable, J.; Harris, P.D.; Lewis, J.W.; Behnke, J.M. (Cambridge University Press, 2006)
The gastro-intestinal (GI) nematode Heligmosomoides polygyrus is an important experimental model in laboratory mice and a well-studied parasite of wood mice in the field. Despite an extensive literature, the taxonomy of this parasite in different hosts is confused, and it is unclear whether laboratory and field systems represent the same or different Operational Taxonomic Units (OTUs). Molecular analyses reveal high sequence divergence between H. p. bakeri (laboratory) and H. p. polygyrus (field); 3% difference in the ribosomal DNA Internal Transcribed Spacers (ITS) and 8.6% variation in the more rapidly evolving mitochondrial cytochrome c oxidase I (COI) gene. The COI sequence of U.K. H. p. polygyrus is more similar to H. glareoli from voles than to H. p. bakeri, while a single isolate of H. p. polygyrus from Guernsey confirms the extent of genetic variation between H. p. polygyrus populations. Analysis of molecular variance demonstrated that mtCOI sequence variation is associated primarily with groups with distinct ITS2 sequences, and with host identity, but is not partitioned significantly with a single combined taxon H. polygyrus incorporating European and North American isolates. We conclude therefore that the laboratory OTUshould be raised to the level of a distinct species, as H. bakeri from the laboratory mouse Mus musculus, and we reject the hypothesis that H. bakeri has diverged from H. polygyrus in the recent past following introduction into America. However, we are unable to reject the hypothesis that H. polygyrus and H. bakeri are sister taxa, and it may be that H. polygyrus is polyphyletic or paraphyletic.